MTBPS 25 Preview: A Costly Primary Surplus - Amra, Rashaad; Chakraborty, Pinaki; Madonko, Thokozile; Willcox, Owen (University of the Witwatersrand, Joahnnesburg, 2025)
South Africa may finally record its first primary surplus in 16 years — but at what cost? The Public Economy Project (PEP)’s updated fiscal outlook shows revenue outperforming the Treasury’s forecast by R53 billion, yet debt is still rising, and social spending is under strain. Years of expenditure restraint have delivered headline stability, but they have also deepened service-delivery pressures. Will this moment be used to rebuild health, education, and social services — or will fiscal consolidation continue to take precedence?
Keywords: MTBPS South Africa Fiscal Policy National Budget Macroeconomic; SDG-10: Reduced inequalities; SDG-10: Reduced inequalities